Usefulness of 3D T1-SPACE in Combination With 3D-TOF MRA for Follow-Up Evaluation of Intracranial Aneurysms Treated With Pipeline Embolization Devices - Shao, Qiuji; Wu, Qiaowei; Li, Qiang; Li, Tianxiao; Li, Li; Chang, Kaitao; Wang, Meiyun (Frontiers in Neurology, 2020)
Object: Follow-up evaluation of intracranial aneurysms treated by flow-diverting stents using MRI is challenging due to the presence of imaging artifacts. This study evaluated 3D T1-SPACE in combination with 3D-TOF sequence for follow-up evaluation of intracranial aneurysms treated with Pipeline embolization devices. Methods: Forty patients with 53 intracranial aneurysms who were treated with Pipeline Embolization Devices from October 2018 to July 2019 were enrolled in this study. All patients were evaluated for aneurysm occlusion and stent patency 4 to 7 months post-treatment using 3D T1-SPACE sequence, 3D-TOF MRA, and DSA examinations. Results: With regards to aneurysm occlusion, the intermodality (DSA and 3D-TOF MRA) agreement was good (κ = 0.755). The specificity of 3D-TOF MRA was 94.4% (34/36), the sensitivity was 76.5% (13/17), the total coincidence rate was 88.7% (47/53). With regards to the patency of the stented arteries after PED treatment, 3D T1-SPACE sequence was more accurate compared to 3D-TOF MRA (Z = −6.283, P < 0.001), with a no-artifact rate of 95.7% (44/46). Conclusions: 3D T1-SPACE sequence provides better image quality and higher accuracy for evaluating stented parent arteries compared to TOF-MRA. 3D-TOF MRA may be valuable in the evaluation of aneurysm occlusion. The combination of these two modalities may be used for long-term follow-up of intracranial aneurysms treated with Pipeline Embolization Devices.